Quality of life in cervical cancer survivors after nerve-sparing radical hysterectomy, conventional radical hysterectomy or concurrent chemoradiotherapy - Li, Wenhui; Wang, Xiuzhen; Wu, Ming; Tan, Xianjie (Frontiers in Oncology, 2025)
BackgroundCervical cancer treatments, including radical hysterectomy and chemoradiotherapy, often lead to urinary, anorectal, and sexual dysfunctions. Nerve-sparing radical hysterectomy (NSRH) aims to reduce such complications, but evidence on long-term quality of life (QoL) remains limited.ObjectiveTo compare QoL outcomes in cervical cancer survivors after NSRH, conventional radical hysterectomy (CRH), or concurrent chemoradiotherapy (CCR).MethodsA cross-sectional study enrolled 427 patients (241 NSRH, 60 CRH, 126 CCR) aged ≤60 years with ≥6 months post-treatment follow-up. QoL was assessed using EORTC QLQ-C30/CX24, Female Sexual Function Index (FSFI), and a self-reported questionnaire. Statistical analyses included ANOVA and chi-square tests.ResultsUrinary symptoms occurred in 27.4% (NSRH), 40.0% (CRH), and 18.6% (CCR) (*p*=0.004). Anorectal symptoms were reported in 23.2% (NSRH), 25.0% (CRH), and 18.6% (CCR) (*p*=0.360). Among sexually active patients, FSFI total scores were higher in NSRH (23.8) vs. CRH (23.3) and CCR (21.6) (*p*=0.026). NSRH also showed superior sexual desire, arousal, and orgasm scores. QoL scores (EORTC QLQ-C30/CX24) indicated better outcomes in constipation (*p*=0.003), lymphedema (*p*<0.001), and sexual activity (*p*=0.027) for NSRH. Subgroup analysis confirmed NSRH alone had fewer complications than NSRH with adjuvant radiation.ConclusionNSRH demonstrates significant advantages in preserving urinary, anorectal, and sexual functions, thereby improving QoL compared to CRH or CCR. It is a preferable option for early-stage cervical cancer, particularly in younger patients.